ANALYSIS OF POST EARTHQUAKE POTENTIAL LIQUEFACTION IN SAMBIK BENGKOL VILLAGE, GANGGA DISTRICT, NORTH LOMBOK REGENCY. - Erick Hansel Santoso; Helmy Darjanto (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734, 2022)
Liquefaction is one of the impacts caused by earthquakes, where liquefaction is a phenomenon of loss of shear stress strength in the soil due to increased pore water pressure caused by earthquake vibration loads. Liquefaction has a fairly detrimental impact on local residents, and can cause damage to infrastructure buildings. This analysis was conducted to determine the potential for liquefaction that occurred after the earthquake that hit Lombok Island on July 29 2018, the earthquake that shook Lombok Island had a magnitude of 6.4 on the Richter scale. As a result, at least 20 people died, 401 others were injured, and more than 10,000 infrastructure buildings were damaged by the earthquake. In this analysis, using the Simplified method proposed by Seed and Idriss (1981), the initial step that must be done is to collect the results of the soil Nspt test in the field, as well as the acceleration of the earthquake that occurred in the field. Then a comparison of the value of the Cyclic Stress Ratio (CSR) with the value of the Cyclic Resistance Ratio (CRR) is made. Based on the calculations carried out on soil testing at the drill point BH-01 and drill point BH-02, it was found that the soil conditions in Sambik Bengkol Village have the potential for liquefaction.